Choosing foods for infants: a qualitative study of the factors that influence mothers. (3rd March 2016) - Boak, R.; Virgo‐Milton, M.; Hoare, A.; de Silva, A.; Gibbs, L.; Gold, L.; Gussy, M.; Calache, H.; Smith, M.; Waters, E.
Abstract: Background: Examining the experiences of parents making food choices for infants is important because ultimately this influences what infants eat. Infancy is a critical period when food preferences and eating behaviour begin to develop, shaping dietary patterns, growth and health outcomes. There is limited evidence regarding what or why foods are chosen for infants. Objective: To describe the experiences of mothers making food choices for their infant children. Methods: Semi‐structured interviews with 32 Australian mothers of infants aged four to 15 months from a range of socioeconomic backgrounds. An inductive thematic analysis through a process of constant comparison was conducted on transcribed interviews. Results: Mothers described many ideas and circumstances which influenced food choices they made for infants. Themes were developed which encapsulate how the wider environment and individual circumstances combine to result in the food choices made for infants. Beliefs, values, norms and knowledge were a central influence on choices. Cost, quality and availabilities of various foods were also key factors. Related to this, and combined with inherent factors such as perishability and infant acceptability, fresh fruits and vegetables were often singled out as an easy or difficult choice. Influences of time, parents' capacities, social connections and different information sources were clearly apparent. Finally infants' own preferences and how parents helped infants with learning to eat were also key influences on food choices. Conclusions: Choosing foods for infants is a complex social practice. An ecological framework depicting the multiple influences on what people eat and sociological theory on food choice regarding the role of 'social structure' and 'human agency' are both applicable to the process of choosing foods for infants. Equity issues may be key regarding the degree to which mothers can choose particular foods for infants (e.g. choosing foods which promote health).